Democratic Republic of Congo Bi-Annual Economic Report, Spring 2011 - World Bank (World Bank, Kinshasa, 2017)
This report is part of a series aimed at monitoring economic developments in the Democratic Republic of Congo (DRC). The main objective of these reports is to provide regular updates on key macroeconomic developments and reform initiatives. The reports focus on macroeconomic developments and key structural reforms that have both significant short and medium term impacts. This report presents a broad overview of macroeconomic, political and structural developments in the DRC up to January 2011 and the outlook for the remainder of 2011. DRC's constitution adopted in 2006 has been revised in January 2011 by Parliament. The main changes to the original texts include the election of the president by a majority in a single round vote. The Congolese authorities have maintained prudent fiscal policies under the International Monetary Fund (IMF) Extended Credit Facility (ECF) program, which has achieved the main objectives of this program in 2010 with an inflation rate (end-of-period) below the target of 9.9 percent. The economy has registered, thanks to the dynamism of the mining sector, a solid growth rate of 7.2 percent compared to 2.8 percent in 2009. Gross Domestic Product (GDP) growth for 2011 is projected to reach 6.5 percent. The country's external position has improved. The current account balance, including grants, improved from a deficit of 10.5 percent of GDP in 2009 to 6.8 percent in 2010. Favorable commodity prices on the world market contributed to this development.